Analysis of Receivables Management to Minimize Uncollectible Receivables at Taum Resort Bali - P A Rahayu; I K Suandi; I M Suarta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
This study aims to determine 1) accounts receivable management at Taum Resort Bali 2) how much receivable loss reserves must be formed by Taum Resort Bali. The data used in this study are aging schedule account receivable, credit sales, total receivables, receivable policies, credit standards and collection of accounts receivable. The measuring instrument used to conduct this research is 5C analysis to analyze crediting standards, receivable policies to analyze compliance collection and collection of accounts receivable, ratios related to accounts receivable such as accounts receivable turnover ratio, ratio of average days of receivable billing, arrears ratio and billing ratio to assess the performance of accounts receivable, a backup method to calculate allowance for receivables losses. The results showed that the overall receivables management was classified as not good after being analyzed using three indicators. The first indicator is fulfilled based on 5C analysis for crediting standards. The second indicator is not met because the collection and collection of receivables is not in accordance with hotel policy. The third indicator is not fulfilled because the results of the performance analysis of accounts receivable using the ratio is not optimal. The amount of uncollectible receivables is high, so the need for the establishment of receivables loss reserves. In 2015 the allowance for receivables losses was set at Rp.43,938,899.00, in 2016 amounted to Rp.63,635,501.00 and in 2017 amounted to Rp.101,042,527.00.